Institutional investors, analyst following, and the January anomaly - Lucy F. Ackert; George Athanassakos (Federal Reserve Bank of Atlanta, 1998)
Studies have documented that average stock returns for small, low-stock-price firms are higher in January than for the rest of the year. Two explanations have received a great deal of attention: the tax-loss selling hypothesis and the gamesmanship hypothesis. This paper documents that seasonality in returns is not a phenomenon observed only for small firms' stock or those with low prices. Strong seasonality in excess returns is reported for a sample of widely followed firms. Sample firms have unusually low excess returns in January, and returns adjust upward over the remainder of the year. These results are consistent with the gamesmanship hypothesis but not the tax-loss-selling hypothesis. As financial institutions rebalance their portfolios in January to sell the stock of highly visible and low-risk firms, there is downward price pressure in January. In addition, the results suggest that firm visibility explains why seasonality in returns is related to firm size and stock price. Once we control for visibility, market value and uncertainty do not appear to be important determinants of seasonality.
Keywords: 330; Financial markets; Seasonal variations (Economics)